Exploring Student Perceptions on Teacher-Students Interaction and Classrooms Learning Environments in Indonesian Mathematics Classrooms - Ida Karnasih; Wahyudi Wahyudi (SEAMEO Regional Centre for QITEP in Mathematics, 2012)
Research studies in education that focus on classrooms and school-level learningenvironments have escalated and produced promising findings that lead to enhancement of the teaching and learning process. The present study reports on the research findings on associations between students’ perceptions of their teacher interaction, classroom learning environment and students’ outcomes. A sample of 946 students from 43 classes in Indonesia schools completed a survey including the Questionnaire on Teacher Interaction (QTI), What is Happening in This Class (WIHIC) and a scale relating to their attitude towards mathematics classes. Statistical analysis shows that the reliability and validity ofthe WIHIC and the QTI were confirmed. Cronbach alpha coefficients ranged from 0.66 to 0.85 and from 0.62 to 0.92 for the actual and preferred versions of the Indonesian version QTI, respectively. For the Indonesian version of WIHIC, Cronbach alpha coefficients of seven scales ranged from 0.80 to 0.91 for actual version, and from 0.78 to 0.92 preferred versions. The relationships of classroom environment and interpersonal teacher behaviour with students' attitudinal outcome were identified. Finally, suggestions on the use of the two instruments for teacher professional development were offered.